Proceedings Proceedings of the 2nd International Workshop on Multimedia Content Analysis in Sports 2019
DOI: 10.1145/3347318.3355518
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Jockeys in a Cluttered Environment with Group Dynamics

Abstract: Figure 1: This project aims to automatically detect and track the jockeys around the turning point of the horse race. The turning point is where the heading direction of jockeys is starting to changes. The sample of turning points are shown on the left side of the figure and the final output of tracking is shown in the right image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The results showed that the centre forwards face the highest demand for high speed runs (HSR). The study conducted in [39] took advantage of known behaviours of jockeys in horse racing to tailor a tracking algorithm based on group dynamics. Our previous research [40] also analysed tracking Taekwondo punches through a combination of a camera and accelerometers.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the centre forwards face the highest demand for high speed runs (HSR). The study conducted in [39] took advantage of known behaviours of jockeys in horse racing to tailor a tracking algorithm based on group dynamics. Our previous research [40] also analysed tracking Taekwondo punches through a combination of a camera and accelerometers.…”
Section: Introductionmentioning
confidence: 99%